“MOHON IZIN, MAS, MBAK”: WUJUD TUTURAN DAN KESANTUNAN BERBAHASA DALAM INTERAKSI RESIDEN - Kurniawati, Atin; Hanafi, Muchtar (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2024)
This article discussed the form of speech acts and language politeness in interaction among residents by focusing on the speeches containing the words "izin (permission)" and "mohon izin (I beg your permission)". Not only for asking permission, these words are used in various speech acts. The data for this study were taken from written conversations among residents through WhatsApp group application. The data were collected using documentation and interview. Then, the data were analyzed using the pragmatic equivalent method. The results of data analysis showed that the words "izin" and "mohon izin" were used in various speech acts, namely assertive, directive, commissive, declarative, and expressive. These words were the embodiment of negative politeness strategies by trying as little as possible to violate the negative face of the interlocutor. The forms of speech in junior and senior resident interactions used a combination of positive politeness strategies and negative politeness strategies. The use of these words was due to the desire to speak politely and to follow the prevailing customs. This study implied the importance of speaking politely in accordance with the customs or conventions that apply to certain communities.Keywords: pragmatics, politeness, residents, speech acts